Optimasi Waktu dan Suhu Refluk Pada Glikolisis Limbah Mikroplastik Polyethylene Terephthalate (PET) Dalam Garam Konsumsi di Kota Padang - Meilindri, Rahmi Aulia; Dewata, Indang (Periodic, 2019)
The use of plastics is increasing every year, causing plastic waste to accumulate. Plastics that are very often found are PET types such as beverage packaging bottles. Plastic waste pollutes the waters because plastic have processes that become microplastic which can pollute marine products, one of which is consumption salt. The handling of PET (polyethylene terephthalate) microplastic can be done by depolymerizing PET plastic polymers into its constituent monomers, namely BHET (Bys-hydroxylethyl terephthalate) monomers using the glycolysis method. The glycolysis method is carried out with ethylene glycol (EG) solvent and Na2CO3 catalyst. PET plastic samples used are PET plastic beverage bottles and salt consumption. The optimum condition of reflux time and reflux temperature of the glycolysis process in this study showed the highest yield of 48.36%, namely at 90 minutes with a temperature of 186 Â° C Characterization of PET glycolysis results with FTIR showed the presence of carboxylic O-H peaks, C = O carbonyl, C-O carboxylates, C-H alkanes, and C-H aromatics which proved that PET polymers had glycolysis process into BHET monomers. The five consumption salt samples used did not show the presence of PET type microplastics by the glycolysis method in 10 grams of consumption salt samples.